INSURANCE LOSS COVERAGE UNDER RESTRICTED RISK CLASSIFICATION: THE CASE OF ISO-ELASTIC DEMAND. Issue 2 (16th February 2016) - Hao, MingJie; Macdonald, Angus S.; Tapadar, Pradip; Thomas, R. Guy
Abstract: This paper investigates equilibrium in an insurance market where risk classification is restricted. Insurance demand is characterised by an iso-elastic function with a single elasticity parameter. We characterise the equilibrium by three quantities: equilibrium premium; level of adverse selection (in the economist's sense); and "loss coverage", defined as the expected population losses compensated by insurance. We consider both equal elasticities for high and low risk-groups, and then different elasticities. In the equal elasticities case, adverse selection is always higher under pooling than under risk-differentiated premiums, while loss coverage first increases and then decreases with demand elasticity. We argue that loss coverage represents the efficacy of insurance for the whole population; and therefore that if demand elasticity is sufficiently low, adverse selection is not always a bad thing.